Cocaine reward and reinstatement in adolescent versus adult rodents - Arguello, Amy A.; Valade, Christian T.; Voutour, Luciano S.; Reeves, Christopher A. (Frontiers in Behavioral Neuroscience, 2024)
Adolescence is a critical juncture when initiation of drug use intersects with profound developmental changes in the brain. Adolescent drug use increases the risk to develop substance use disorders (SUDs) later in life, but the mechanisms that confer this vulnerability are not understood. SUDs are defined by cycles of use, abstinence, and relapse. Intense craving during drug-free periods is often triggered by cues and environmental contexts associated with previous use. In contrast to our understanding of stimuli that elicit craving and relapse in adults, the behavioral processes that occur during periods of abstinence and relapse in adolescents are poorly understood. The current mini-review will summarize findings from preclinical rodent studies that used cocaine conditioned place preference and operant cocaine self-administration to examine subsequent effects on reward, relapse and incubation of craving.